Journey to vaccination: a protocol for a multinational qualitative study. Issue 1 (31st January 2014) - Wheelock, Ana; Miraldo, Marisa; Parand, Anam; Vincent, Charles; Sevdalis, Nick
Abstract : Introduction: In the past two decades, childhood vaccination coverage has increased dramatically, averting an estimated 2–3 million deaths per year. Adult vaccination coverage, however, remains inconsistently recorded and substandard. Although structural barriers are known to limit coverage, social and psychological factors can also affect vaccine uptake. Previous qualitative studies have explored beliefs, attitudes and preferences associated with seasonal influenza (flu) vaccination uptake, yet little research has investigated how participants' context and experiences influence their vaccination decision-making process over time. This paper aims to provide a detailed account of a mixed methods approach designed to understand the wider constellation of social and psychological factors likely to influence adult vaccination decisions, as well as the context in which these decisions take place, in the USA, the UK, France, India, China and Brazil. Methods and analysis: We employ a combination of qualitative interviewing approaches to reach a comprehensive understanding of the factors influencing vaccination decisions, specifically seasonal flu and tetanus. To elicit these factors, we developed the journey to vaccination, a new qualitative approach anchored on the heuristics and biases tradition and the customer journey mapping approach. A purposive sampling strategy is used to select participants who represent a range of key sociodemographic characteristics. Thematic analysis will be used to analyse the data. Typical journeys to vaccination will be proposed. Ethics and dissemination: Vaccination uptake is significantly influenced by social and psychological factors, some of which are under-reported and poorly understood. This research will provide a deeper understanding of the barriers and drivers to adult vaccination. Our findings will be published in relevant peer-reviewed journals and presented at academic conferences. They will also be presented as practical recommendations at policy and industry meetings and healthcare professionals' forums. This research was approved by relevant local ethics committees.